The Impact of TAM, Social Influence, and Information Quality on Purchase Intention in E-commerce - Lily Purwianti; Listia Nurjanah; Katherine Katherine; Robin Chen (Jurnal Organisasi dan Manajemen, 2024)
Purpose – This study analyzes the impact of  TAM (Technology Acceptance Model), social influence, and quality of information on purchase intention with mediation of e-commerce attitude. Methodology– The study procedures were carried out using quantitative method, and data were collected with various instruments, and analyzed applying structural equation modeling technique (PLS-SEM). A total of 349 consumers who were familiar with e-commerce applications were then selected with purposive sampling using non-probability methods. Findings—The perceived usefulness, information quality, and social influence had a significant effect on attitude, while attitude had an impact on purchase intention. In addition, perceived ease of use was reported to have no significant impact. The results also showed that attitude could mediate the relationship between perceived usefulness, information quality, and social influence regarding purchase intention. However, the variable did not mediate the impact of perceived ease of use on purchase intention. Originality – This analysis developed TAM theory by adding new variables, namely social influence and information quality. Since social influence played a role in motivating technology use, information quality was also considered an essential variable in online platforms.